Visualisasi Interaktif Permukaan dalam Ruang Tiga Dimensi: Analisis Geometris dengan GeoGebra - Bali Sahputri Tarigan; Lauren Teresia Tamba; Tantory Yahya Purba (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Surfaces in three-dimensional space can be represented through explicit, parametric and implicit equations, which describe the relationship between the variables x, y and z. Graphs of linear equations produce flat planes, while quadratic equations form objects such as spheres or ellipsoids. In this research, a theoretical approach is combined with interactive visualization to analyze various surface shapes. Through the use of GeoGebra software, this analysis makes it easier to understand surface orientation and shape, such as normal vectors and curvature, as well as applications in vector fields. This research also investigates the concepts of Cartesian coordinates in three-dimensional space, by depicting surfaces in the form of graphs of functions of two variables. It is hoped that the results of this research can provide deeper insight into the geometric properties of surfaces and how to visualize them effectively in mathematics and physics applications.